Greetings from the Director of the Center of Excellence for Healthcare and Pharmaceutical Professionals - Juozas Ruolia, Director of Center of Excellence of Healthcare and Pharmacy Specialists (Slauga. Mokslas ir praktika, 2020)
Greetings from the Director of the Center of Excellence for Healthcare and Pharmaceutical Professionals.